Obraz kartograficzny Szadku w XIX w. - Bartoszewicz, Agnieszka (Biuletyn Szadkowski, 2008)
Szadek – a town fulfilling in the past important administrative and socio-economic functions – is found on almost all maps of old Poland’s territory. Therefore plentiful archival material is kept in the Central Archive of Old Documents in Warsaw and Public Records Office in Łódź. It allows various studies on the history of Szadek and its inhabitants to be conducted, but the town’s spatial structure – both its origins and stages of development – can be studied on the basis of cartographic sources from the 19th century, especially several hand-drawn general plans. The article presents cartographic material kept in the Central Archive of Old Documents, with a particular focus on three plans of the town drawn up in the mid-19th century. They make it possible to trace changes in the spatial structure of the town and the character of construction work carried out at that time.